The Madrasa in Indonesia (Authority, Knowledge and Discourse Surrounding its Development) - Kurniawan, Syamsul; Miftah, Muhammad (Program Studi Pendidikan Agama Islam, 2020)
The focus of this paper is the madrasa in Indonesia and its development which is examined from the perspective of Michel Foucault regarding their authority, knowledge and discourse. The madrasa’s performance, which is still relatively low and unable to compete with public schools or pesantrens (Islamic Boarding Schools), will be examined from this perspective. This paper departs from the study of literature with a historical-sociological approach. The sources of the data come from the literature related to the history and development of madrasas. From Foucoult's perspective, the performance of the madrasa–which in its development shows a decline trend and is of relatively low quality and less competitive compared with general schools or pesantrens– is closely related to power, knowledge and discourse factors. My argument is supported by the evidence that there is no an established “blueprint” for the supervision and development of madrasas in Indonesia, in contrast to schools or pesantrens. Likewise, the problem of interplay of madrasa policies in the integration of the national education system has put the madrasa in the midst of domination of schools and pesantrens, especially in the midst of society since the appreciation and level of community participation in the madrasa are not very encouraging. In addition, there is an opinion among the public which perceives the madrasa as the second educational institution after schools or pesantrens. This opinion is, of course, supported by empirical data, such as research from Nur Hamzah (2017) and Sukino (2017) which examined the madrasas in West Kalimantan Province, and revealed the poor quality of some madrasas in this area, which in my opinion is the